Science return of probing magnetospheric systems of ice giants - Cao, Xin; Chu, Xiangning; Hsu, Hsiang-Wen; Cao, Hao; Sun, Weijie; Liuzzo, Lucas; Halekas, Jasper; Paty, Carol; Chu, Feng; Agiwal, Omakshi; Blum, Lauren; Crary, Frank; et al. (Frontiers in Astronomy and Space Sciences, 2024)
The magnetospheric systems of ice giants, as the ideal and the unique template of a typical class of exoplanets, have not been sufficiently studied in the past decade. The complexity of these asymmetric and extremely dynamic magnetospheres provides us a great chance to systematically investigate the general mechanism of driving the magnetospheres of such common exoplanets in the universe, and the key factors of influencing the global and local magnetospheric structures of this type of planets. In this paper, we discuss the science return of probing magnetospheric systems of ice giants for the future missions, throughout different magnetospheric regions, across from the interaction with upstream solar wind to the downstream region of the magnetotail. We emphasize the importance of detecting the magnetospheric systems of ice giants in the next decades, which enables us to deeply understand the space environment and habitability of not only the ice giants themselves but also the analogous exoplanets which are widely distributed in the universe.